2011
DOI: 10.1590/s1806-37132011000300016
|View full text |Cite
|
Sign up to set email alerts
|

Disfunção muscular periférica em DPOC: membros inferiores versus membros superiores

Abstract: In patients with COPD, the degree of functional impairment appears to differ between the upper and lower limbs. Significant dyspnea and fatigue have been reported by these patients when performing tasks with unsupported upper limbs and two mechanisms have been proposed to explain this fact: neuromechanical dysfunction of respiratory muscles; and changes in lung volume during such activities. The neuromechanical dysfunction seen in COPD patients during this type of exercise is related to changes in the breathin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 55 publications
0
25
0
5
Order By: Relevance
“…The degree of functional impairment between the upper and lower limbs differs among patients with COPD. Lower limb muscles appear to be associated with muscle endurance and daily functional performance, whereas upper limb muscles have been correlated with both physical and pulmonary functional indicators 26. Raftery (1995) suggested that a lower BIC value of 2–6 is a positive evidence for a model 20.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of functional impairment between the upper and lower limbs differs among patients with COPD. Lower limb muscles appear to be associated with muscle endurance and daily functional performance, whereas upper limb muscles have been correlated with both physical and pulmonary functional indicators 26. Raftery (1995) suggested that a lower BIC value of 2–6 is a positive evidence for a model 20.…”
Section: Discussionmentioning
confidence: 99%
“…(2) However, Dal Corso et al (1) and Swinburn et al (3) reported that step climbing involves working against gravity and the use of muscle groups that are not frequently used during activities of daily living, which produces physiological responses that are different from those of the walk test, making the metabolic and ventilatory demands of step climbing more intense. In addition, it should be borne in mind that the leg muscles in patients with COPD are impaired in terms of strength and endurance because of a reduction in muscle mass and aerobic capacity, (4) compromising performance. For this reason, it is important that leg muscle exercises be performed to improve the functional performance of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance training typically includes a combination of resistance exercises for upper-body, lower-body and trunk muscles with an emphasis on lower-body resistance training [1,2]. Little is known about the unique contribution of upper-body resistance training to outcomes such as symptoms and functional performance [3] and about long term maintenance after completion of a structured program of resistance training in people with COPD.…”
Section: Introductionmentioning
confidence: 99%
“…There are differences in the morphological adaptations to COPD between the muscles of the upper body and lower body [3]. Greater fatigability has been observed for the upper extremity muscles.…”
Section: Introductionmentioning
confidence: 99%